THE EFFECT OF RETURN ON ASSETS ON THE PRICE OF SHARE WITH DIVIDEND PAYOUT RATIO AND DEBT TO EQUITY RATIO AS THE MODERATING VARIABEL. (Manufacture Companies Listed in Indonesia Stock Exchange (ISE) in 2012-2015) - mulyati mulyati (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research is aimed at determining the effect of return on assets (ROA) on the price of share with dividend payout ratio (DPR) and debt to equity ratio (DER) as the moderating variabel in manufacture companies listed in Indonesia Stock Exchange (ISE) in 2012-2015.The population of this research are manufacture companies listed in Indonesia stock Exchange (ISE) in 2012-2015. The samples are 10 manufacture companies selected through purposive sampling. The data were collected through documentation. The data were examined using Moderated Regretion Analysis with SPSS.The research showed that: (1) ROA has negative and significant effect on the share price, (2) DPR has positive and significant effect in moderating the share price, (3) DER has negative but not significant effect in moderating the effect of ROA on the share price in manufacture companies listed in ISE in 2012-2014.Keywords: return on assets (ROA), dividend payout ratio (DPR), debt to equity ratio (DER), share price.